Educational intervention to improve menstrual hygiene management in adolescent girls in Kalimantan, Indonesia - Nastit, Aria Aulia; Triharini, Mira; Pratiwi, Ananda Hanna; Kamel Gouda, Amel Dawod (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the effect of health education on menstrual hygiene management in adolescents. Methods: The quasi-experimental study was conducted from April to July 2021 in Sampit, Kalimantan, Indonesia, after approval from ethics review committee of the Nursing University of Airlangga, Surabaya, East Java, Indonesia. The sample comprised grade VII female students at a public junior high school in Sampit. The sample was divided into intervention group A and control group B. Group A was given a health education intervention through video conferences in two meetings and was given a leaflet after each meeting which lasted 90 minutes. The control group was only given a leaflet. Baseline and post-intervention data was compared. Data was analysed using SPSS 16. Results: There were 70 subjects; 35(50%) in each of the two groups. The age range was 12-14 years, with 25(71.4%) subjects in group A and 28(80%) in group B being aged 13 years. The age of menarche was 12 years for 17(48.6%) subjects in each of the two groups. Knowledge level of group A increased significantly post-intervention (p<0.05), but group B showed no significant difference (p=0.144). Conclusion: Health education on menstrual hygiene management was found to have a beneficial influence on knowledge and attitudes among adolescents. Keywords: Adolescent, Hygiene, Menstruation, Health education, Health knowledge, Attitudes, Practice.